Leadership Style and Organizational Communication Patterns: a Qualitative Descriptive Study - Alum Kusumah; Khusnul Fikri (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2021)
This study aims to examine the leadership style and organizational communication pattern in the Converting Department, PT. IPP. The leadership elements described are at the general manager and manager levels. The research method used is descriptive and qualitative methods. The data used are primary and secondary data collected through observation supported by interviews, library research, and document analysis. Data and information obtained from the employee of Converting Department, PT. IPP, with as many as 22 informants consisting of the employee from each level of position. Leadership style at the Converting Department, PT. IPP, is centered on characteristics of existing leaders with the most dominant leadership style is exploitive-authoritative because it is attached to the top leader. The existing leadership style is not quite ideal to face challenges in the future. For internal organizational communication, patterns occur either downward communication, upward, horizontal and cross-channel.